A influência da atividade exploratória na descoberta de Affordancesdurante o desenvolvimento do alcance - Camila Bretas Mourao (2010)
Introduction: The exploratory activity for the development of the reach can be visual and/or manual. The practical of exploratory activity provides profits of motor and perceptual capacities that will make possible to the baby the discovery of affordances. When interacting with the environment and discovering affordances, the baby discloses an adaptive behavior that will evidence its development. The objective of this study was to investigate the relation between exploratory activities and the discovery of affordances touchable and hittable and posterior development of the adaptive behavior of the hit in the target, during the development of the reach in babies of 4 to 8 months of life. Materials and Method: This is a longitudinal study, in which thirteen babies had been enlisted by convenience. They had data collected of each baby biweekly, of 4 to 8 months of life, totalizing nine collections. The babies interacted spontaneously with a spherical target that turns around the proper axle, offering the possibilities of touch and hit, per 90 seconds, while they were filmed by two digital cameras. Visual and manual exploratory activities of the target, as well as the attempts of reach and of reach types as touch and hit had been extracted, of the nine longitudinal collections, through video-analysis by five researchers (ICC=0,8). Survival analysis investigated the time until the first occurrence of the interest events (touch and hit) and the Kaplan-Meier method was used to compare the influence of the exploratory activities (predictors) in the discovery of affordances touchable and hittable. Multilevel models had tested the influence of the exploratory activities in the occurrence of hits throughout the time. Results and Discussion: The exploratory activity became gradually multimodal: while the pure visual exploration diminished, it was incorporated the manual exploration. The babies discovered affordances touchable and hittable up to 5,5 months of age; those that had discovered affordances earlier, explored less the target. Touch and hit are distinct forms of reach and the first one does not influence the improvement of the second. The reduction of 1% in the visual exploration increased in 2,2% the possibility to carry through hit. The increase of 1 attempt of hit increased 3,6% the possibility of occurrence of hits, while the increase of 1 attempt of touch moved away in 0,9% the possibility from occurrence from hits. Conclusion: The discovery of affordances touchable and hittable seemed to happen for the confluence of the physical properties of the object with the capacities of the baby to quickly extract the relevant information through multimodal exploratory activity, without necessity of previous practice. However, the relation between exploratory activity and discovery of affordances were distinct of the relation between exploratory activity and the development of the hit. For the development of the hit, practical of more multimodal and specific exploratory activities seem to be important.